Expectations of Low cost airline staff toward digital innovation - Juntarapinyo, Vasita; Kaewnuch, Kanokkarn (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2022)
Covid-19 has dramatically decreased aviation industries including those in Thailand. This paper focuses solely on Thai low cost airlines by discussing and analyzing preparation plans to deal with Covid-19 using the means of digital innovation through the cabin crew’s expectations. The researcher proposes digital innovation could help Thailand low cost carriers to survive during and after the pandemic. Therefore, a survey was designed and conducted among crew in Thailand This paper consists of an introduction followed by a literature review discussing information about digital innovations. The latter part explains methods used in the study, data interpretation, then concludes. The study will benefit other researchers to study and investigate in greater detail concerning related work about innovation for airlines and the aviation industry postCovid-19. The time might have affected the results of the study as Covid-19 has not disappeared yet. Hence, researchers can use this study as a fundamental component in arranging concepts for further studies. Secondly, the study will benefit low cost airline companies especially in the area of directing better preparation postCovid-19. Low cost carriers can use this study to integrate with the company policy to find the best strategies and preparation to survive and meet employee expectations.